Measuring Success: Evaluating the Impact of Industry Involvement on the Sustainability of Work-Based Learning Programs in Polytechnics - Suhaini Mat Daud; Nor Ifeezul Haikal Mohd Irwan (UNIVERSITAS SERAMBI MEKKAH, 2024)
Work-based learning (WBL) is an educational approach that integrates theoretical knowledge and work experience in the industry, preparing students with relevant skills to enter an increasingly complex job market. The success of the work-based learning approach in producing skilled workforce cannot be denied. The involvement of industries plays a crucial role in ensuring that work-based learning is continuous and sustainable. Industries are not only involved at the initial stage or during the formation of WBL education programs but also continue to contribute and support throughout the learning period and even after students graduate from Polytechnics. Therefore, a study has been conducted to measure the level of industry involvement in the sustainability of the implementation of work-based learning (WBL) in Malaysian Polytechnics. Industry involvement in the context of this study is measured based on four factors: governance, organizational motivation, facilities, and curriculum understanding. This study was conducted using a quantitative research method where the respondents consisted of 91 WBL supervising lecturers. IBM SPSS version 26 was used to analyze the data of this study. The findings indicate that the level of industry involvement in the sustainability of the WBL approach in polytechnics is high.